Reinventing jihād : jihād ideology from the conquest of Jerusalem to the end of the Ayyūbids (c. 492/1099-647/1249) - Goudie, Kenneth A., (The Muslim World in the Age of the Crusades;, 2019)
In Reinventing Jihād, Kenneth A. Goudie provides a detailed examination of the development of jihād ideology from the Conquest of Jerusalem to the end of the Ayyūbids (c. 492/1099-647/1249). By analysing the writings of three scholars - Abū al Ḥasan al Sulamī (d. 500/1106), Ibn ʿAsākir (d. 571/1176), and ʿIzz al-Dīn al-Sulamī (d. 660/1262) - Reinventing Jihād demonstrates that the discourse on jihād was much broader than previously thought, and that authors interwove a range of different understandings of jihād in their attempts to encourage jihād against the Franks. More importantly, Reinventing Jihad demonstrates that whilst the practice of jihād did not begin in earnest until the middle of the twelfth century, the same cannot be said about jihād ideology: interest in jihād ideology was reinvigorated almost from the moment of the arrival of the Franks.